The wave energy converter control competition - Ringwood, John; Ferri, Francesco; Tom, Nathan; Ruehl, Kelley M.; Faedo, Nicolás; Bacelli, Giorgio; Yu, Yi-Hsiang; Coe, Ryan G. (ASME, 2019)
Over the past two years, a wave energy converter control systems competition (WECCCOMP) has been in progress, with the objective of comparing different wave energy converter (WEC) control paradigms on a standard benchmark problem. The target system is a point absorber, corresponding to a single float with an absolute reference, of the WaveStar WEC prototype. The system was modelled in WEC-Sim, with the hydrodynamic parameters validated against tank test data. Competitors were asked to design and implement a WEC control system for this model, with performance evaluated across six sea states. The evaluation criteria included a weighted combination of average converted power, peak/average power, and the degree to which the system physical constraints were exploited or temporarily exceeded. This paper provides an overview of the competition, which includes a comparative evaluation of the entries and their performance on the simulation model. It is intended that this paper will act as an anchor presentation in a special session on WECCCOMP at OMAE 2019, with other papers in the special session contributed by the competitors, describing in detail the control algorithms and the results achieved over the various sea states.